2014
DOI: 10.3171/2014.1.jns131431
|View full text |Cite
|
Sign up to set email alerts
|

Prospective natural history study of central nervous system hemangioblastomas in von Hippel-Lindau disease

Abstract: Object The tumors most frequently associated with von Hippel-Lindau (VHL) disease are hemangioblastomas. While they are associated with significant neurological impairment and mortality, their natural history and optimal management have not been fully defined. Methods Patients with VHL were enrolled in a prospective study designed to define the natural history of CNS hemangioblastomas. In the present analysis, serial imaging, laboratory, genetic, and clinical data were evaluated in those with at least 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
192
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(205 citation statements)
references
References 34 publications
4
192
3
6
Order By: Relevance
“…Consistent with our results, Lonser et al 14 recently found that established CNS hemangioblastomas grew at significantly different rates depending on their anatomical location in the CNS. The contrasting manifestation rate profiles found in this study point toward two distinct development patterns at the two anatomical locations, although tumors in both locations are identical in their histopathology and origin.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Losupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, Lonser et al 14 recently found that established CNS hemangioblastomas grew at significantly different rates depending on their anatomical location in the CNS. The contrasting manifestation rate profiles found in this study point toward two distinct development patterns at the two anatomical locations, although tumors in both locations are identical in their histopathology and origin.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Losupporting
confidence: 93%
“…Previous studies of vHL manifestation development have predominantly focused on either total or cumulative manifestation frequencies or on growth patterns of individual tumors. 6,7,[11][12][13][14][15] The few studies that have assessed growth patterns of vHL tumors have mostly assessed growth rates of individual tumors in relation to observation time regardless of the patients' ages. 12,13 Furthermore, many of these studies have solely included patients with clinical vHL or a specific manifestation type and have not taken asymptomatic VHL mutations carriers into account, 6,[12][13][14] which may bias the frequency estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioblastoma yra nepiktybinis, lėtai augantis kraujagyslinės kilmės centrinės nervų sistemos navikas, dažniausiai nustatomas smegenėlėse, smegenų kamiene ir nugaros smegenyse [1][2][3][4][5][6][7]. Hemangioblastoma vystosi iš hemangioblastų, todėl gali plisti su krauju ar transformuotis į pirmines endotelines ląsteles [2].…”
Section: įVadasunclassified
“…Tai stipriai vaskuliarizuotas navikas, histologiškai gėry-binis, bet sukeliantis neurologinius deficitus ir susijęs su ženkliu mirštamumu [6,17]. Klinikinis pasireiškimas priklauso nuo naviko dydžio, lokalizacijos ir išplitimo į galvos ir nugaros smegenis [1][2][5][6]9]. Dažniausi simptomai yra galvos skausmai, ūžesys ausyse, galvos svaigimas, rankų ir kojų skausmai ir silpnumas, sensoriniai deficitai, eisenos sutrikimai ir spinalinė ataksija, dismetrija, nistagmas, hidrocefalija ir inkontinencija [1][2][5][6]9].…”
unclassified
See 1 more Smart Citation